2017
DOI: 10.1093/mnras/stx294
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of LINER galaxies within the galaxy group environment

Abstract: We study the properties of a sample of 3967 LINER galaxies selected from SDSS-DR7, respect to their proximity to galaxy groups. The host galaxies of LINER have been analysed and compared with a well defined control sample of 3841 non-LINER galaxies matched in redshift, luminosity, colour, morphology, age and stellar mass content. We find no difference between LINER and control galaxies in terms of colour and age of stellar population as function of the virial mass and distance to the geometric centre of the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 54 publications
(59 reference statements)
5
20
0
Order By: Relevance
“…The AGN ionizing field is likely not dominant in the optical domain, but according to our statistical study, the nuclear and jet activity must be present. This is also in agreement with the studies of Coldwell et al (2017Coldwell et al ( , 2018 where they find that LINERs are redder and older than the control sample of galaxies in environ-ments of different density. They also show that LINERs are likely to populate low-density regions in spite of their elliptical morphology, that is, their occurrence in low-density galaxy groups is two times higher than the occurrence of the control, non-LINER galaxies.…”
Section: Flat and Inverted Spectral Index Towards Liners: Implicationsupporting
confidence: 92%
See 1 more Smart Citation
“…The AGN ionizing field is likely not dominant in the optical domain, but according to our statistical study, the nuclear and jet activity must be present. This is also in agreement with the studies of Coldwell et al (2017Coldwell et al ( , 2018 where they find that LINERs are redder and older than the control sample of galaxies in environ-ments of different density. They also show that LINERs are likely to populate low-density regions in spite of their elliptical morphology, that is, their occurrence in low-density galaxy groups is two times higher than the occurrence of the control, non-LINER galaxies.…”
Section: Flat and Inverted Spectral Index Towards Liners: Implicationsupporting
confidence: 92%
“…The interpretation and the nature of LINERs remains still unclear and several recent studies have attempted to shed more light on their characteristics and the potential effect of the environment (Singh et al 2013;Coldwell et al 2017Coldwell et al , 2018. The fact that 50% of LINERS in both frequency ranges have flat to inverted spectral indices points to the activity of the nucleus and the dominant contribution of the core and the jet radio emission to the overall radio emission of LINER galaxies.…”
Section: Flat and Inverted Spectral Index Towards Liners: Implicationmentioning
confidence: 99%
“…Different studies demonstrated that the host galaxies of LINERs have a bulge-type morphology being more massive and luminous than a general galaxy sample (Yan et al 2006;Kewley et al 2006;Capetti & Baldi 2011;Coldwell et al 2017). This early-type galaxies are commonly found in dense galaxy environment as it is suggested by the morphology-density relation (Dressler 1980;Domínguez, Muriel & Lambas 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Then, if the photoionization from AGNs is one of the mechanisms for the LINER emission we could expect that, at least, LINERs follow a similar trend that Seyfert 2 galaxies. On this way, Coldwell et al (2017) analysed the occurrence of SDSS-DR7 LINER galaxies with respect to their proximity to galaxy groups. The main results have shown that a higher percentage of LINER can be found populating low-density environment.…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies conclude a higher active galactic nucleus occurrence in lower/medium density environments at low redshifts. (Kauffmann et al 2004;Choi et al 2009;Sabater et al 2013;Coldwell et al 2014Coldwell et al , 2017. In addition, galaxy-galaxy interactions may produce gravitational instabilities providing gas to the most central regions of the galaxy and the growth by accretion of the central black holes.…”
Section: Introductionmentioning
confidence: 99%